2013
DOI: 10.1016/j.cub.2013.09.048
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Oct4/POUV-Dependent Network Links Adhesion and Migration to Progenitor Maintenance

Abstract: SummaryBackgroundThe class V POU domain transcription factor Oct4 (Pou5f1) is a pivotal regulator of embryonic stem cell (ESC) self-renewal and reprogramming of somatic cells to induced pluripotent stem (iPS) cells. Oct4 is also an important evolutionarily conserved regulator of progenitor cell differentiation during embryonic development.ResultsHere we examine the function of Oct4 homologs in Xenopus embryos and compare this to the role of Oct4 in maintaining mammalian embryo-derived stem cells. Based on a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 54 publications
10
44
0
Order By: Relevance
“…The ESC model, on the other hand, has a reprogramming efficiency that peaks for some reprogramming forces and then decreases. This corresponds well to the experimental and computational result that reprogramming works best for a limited range of over-expression [38, 39, 40]. In plants, ectopic WUS, either directly or via removing the function of CLV3 has been used to create ectopic stem cells in vivo [16, 41, 42].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The ESC model, on the other hand, has a reprogramming efficiency that peaks for some reprogramming forces and then decreases. This corresponds well to the experimental and computational result that reprogramming works best for a limited range of over-expression [38, 39, 40]. In plants, ectopic WUS, either directly or via removing the function of CLV3 has been used to create ectopic stem cells in vivo [16, 41, 42].…”
Section: Resultssupporting
confidence: 73%
“…The small variations of wiring in the core networks of the two stem cell kingdoms could be due to players, which appear to be specialized, being actually able to hold multiple roles in the mammalian stem cell system e.g. Oct4 [40, 49], Mbd3 [47, 48], while plants are known to use different proteins from the same protein families in regulating differentiation in different tissues [25]. In particular, we found that the incoherent feed forward motif between Oct4 and Nanog could be perturbed, leading to more similar reprogramming behaviour as in plants.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that knocking down pou5f3 in Sall4 morphants would restore posterior neural identity. To this end, we co-injected MOs targeting the three pou5f3 homologs (Morrison and Brickman, 2006;Livigni et al, 2013) along with Sall4 MOs. Consistent with the results described above, knockdown of Sall4 resulted in loss of posterior hoxb9 (Fig.…”
Section: Sall4 Is Required For Posterior Neural Differentiation But Nmentioning
confidence: 99%
“…The Sall4 MO oligonucleotide (5 0 -GCCAATTATTCCCTTTCTCCACC-AC-3 0 ; Gene Tools) and the Pou5f3 MOs (a gift from Joshua Brickman) (Livigni et al, 2013;Morrison and Brickman, 2006) were injected in 5 or 10 nl along with fluoresceinated control MO (Gene Tools) to serve as a tracer.…”
Section: Rna and Mo Microinjectionsmentioning
confidence: 99%
“…Based on these assays, orthologues of POU5F1 and POU5F3 show varying degrees of functional conservation in inducing pluripotency and supporting self-renewal. In particular, in Xenopus, which has three POU5F3 genes ( pou5f3.1, pou5f3.2 and pou5f3.3) that presumably arose by tandem duplication, the expression pattern and activity of these genes have diversified such that only one of them -pou5f3.1 -is expressed in primordial germ cells and has 'OCT4-like' activity in both reprogramming and ESC self-renewal (Livigni et al, 2013;Venkatarama et al, 2010;Tapia et al, 2012 Tapia et al, 2012). Zebrafish pou5f3 also participates in zygotic genome activation (Lee et al, 2013;Leichsenring et al, 2013) and, although this has not been explored in mammals, the observation that mouse embryos develop to the blastocyst stage in the absence of both maternal and zygotic Pou5f1 (Frum et al, 2013;Le Bin et al, 2014;Nichols et al, 1998;Wu et al, 2013) suggests that this function might not be conserved.…”
mentioning
confidence: 99%